2015
DOI: 10.1053/j.gastro.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, Genetic, and Cellular Bases for Treating Eosinophilic Esophagitis

Abstract: Eosinophilic esophagitis (EoE) was historically distinguished from gastroesophageal reflux disease on the basis of histology and lack of responsiveness to acid suppressive therapy, but it is now appreciated that esophageal eosinophilia can respond to proton pump inhibitors. Genetic and environmental factors contribute to risk for EoE—particularly early-life events. Disease pathogenesis involves activation of epithelial inflammatory pathways (production of eotaxin-3 [encoded by CCL26]), impaired barrier functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
157
2
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(167 citation statements)
references
References 99 publications
(169 reference statements)
3
157
2
5
Order By: Relevance
“…Our fi ndings show that both genetic (a CYP2C19 rapid metabolizer genotype) and environmental (rhinoconjunctivitis, likely refl ecting exposure to airborne allergens) factors were the most infl uential factors determining recurrence. Th is observation, the fi rst of its kind in PPI-REE, appears to mirror the interacting genetic and environmental factors that contribute to the pathogenesis of EoE ( 18 ). In this regard, it is tempting to speculate that responsiveness to PPI in PPI-REE might be modulated by the interaction of acid exposure (increased due to ineffi cacy of PPI in CYP2C19 r apid metabolizers) and esophageal aeroallergen exposure.…”
Section: Long-term Outcome In Ppi-responsive Esophageal Eosinophiliamentioning
confidence: 99%
“…Our fi ndings show that both genetic (a CYP2C19 rapid metabolizer genotype) and environmental (rhinoconjunctivitis, likely refl ecting exposure to airborne allergens) factors were the most infl uential factors determining recurrence. Th is observation, the fi rst of its kind in PPI-REE, appears to mirror the interacting genetic and environmental factors that contribute to the pathogenesis of EoE ( 18 ). In this regard, it is tempting to speculate that responsiveness to PPI in PPI-REE might be modulated by the interaction of acid exposure (increased due to ineffi cacy of PPI in CYP2C19 r apid metabolizers) and esophageal aeroallergen exposure.…”
Section: Long-term Outcome In Ppi-responsive Esophageal Eosinophiliamentioning
confidence: 99%
“…Concerning the pathogenesis of PPI-responsive eosinophilic esophagitis, it has been hypothesized that a peptic and allergic hypersensitivity component is present. This fact has been interpreted as an indicative that PPI-responsive eosinophilic esophagitis and EoE represent different stages of a single nosologic entity (22) . Eosinophils are not normally seen in healthy esophageal mucosa, but as an evidence of esophageal inflammation (7) .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have investigated the role of special staining to identify inflammatory mediators and eosinophil derived elements, aimed at increasing the predictive value of the differential diagnosis. Some reports have indicated that a higher count of mast cells in the esophageal mucosa may be a diagnostic marker for EoE and PPI-responsive eosinophilic esophagitis (1,4,10,18,19,22) . The aim of this study was to confirm that the presence of mast cells in the esophageal epithelium of children, identified by immunohistochemistry for tryptase, may be associated with EoE and/or PPI-responsive eosinophilic esophagitis and can be useful in the differential diagnosis with RE.…”
Section: Mast Cells Distinguish Eosinophilic Esophagitis In Pediatricmentioning
confidence: 99%
“…This disease is associated with a variety of mendelian genetic based disorders [41] . The most frequent associations of EoE are with hereditary collagen disorders such as Marfan and Ehlers-Danlos syndromes with an incidence of about 1% [42] .…”
Section: Genetic Vs Environmental Etiological Factorsmentioning
confidence: 99%